LKB1 regulates ILC3 postnatal development and effector function through metabolic programming - Zhang, Huasheng; Zhao, Linfeng; Zhang, Qingbing; Hu, Lin; Su, Xiaohui; Sun, Jiping; Shen, Lei (Frontiers in Immunology, 2025)
IntroductionGroup 3 Innate Lymphoid Cells (ILC3s) are important for maintaining intestinal homeostasis and host defense. Emerging studies have shown that metabolic regulation plays a crucial role in regulating ILC3 activation and function. However, the role of Liver Kinase B1 (LKB1), a key metabolic regulator, in regulating ILC3 function and intestinal immunity remains poorly understood.MethodsTo investigate the role of LKB1 in intestinal ILC3s, we generated LKB1 conditional knockout mice by crossing Rorccre and Stk11flox/flox mice. Cell number and cytokine production was examined using flow cytometry. Citrobacter rodentium infection model were used to determine the role of LKB1 in intestinal defense. RT-qPCR, flow cytometry and immunohistochemistry were used to assess the intestinal inflammatory responses.ResultsIn this study, we show that LKB1 is essential for ILC3 postnatal development, effector function, and intestinal immunity. LKB1-deficient mice exhibit a marked decrease in ILC3 number at 2 -3 weeks after birth. Ablation of LKB1 in ILC3s results in diminished IL-22 production and less protection against Citrobacter rodentium infection. Moreover, LKB1 deficiency leads to impaired cell metabolism, as indicated by reduced glycolysis and oxidative phosphorylation and less mitochondrial mass. Together, our data demonstrate that LKB1 promotes ILC3 postnatal development and effector function to maintain intestinal immune homeostasis.DiscussionOur findings reveal that LKB1 is a key regulator of intestinal ILC3 development, function, and metabolism, thereby linking metabolic control to intestinal immune homeostasis and offering potential therapeutic implications.